Extensive Differential Splicing Underlies Phenotypically Plastic Aphid Morphs. (2nd May 2018) - Grantham, Mary E; Brisson, Jennifer A
Abstract: Phenotypic plasticity results in a diversity of phenotypes from a single genotype in response to environmental cues. To understand the molecular basis of phenotypic plasticity, studies have focused on differential gene expression levels between environmentally determined phenotypes. The extent of alternative splicing differences among environmentally determined phenotypes has largely been understudied. Here, we study alternative splicing differences among plastically produced morphs of the pea aphid using RNA-sequence data. Pea aphids express two separate polyphenisms (plasticity with discrete phenotypes): a wing polyphenism consisting of winged and wingless females and a reproduction polyphenism consisting of asexual and sexual females. We find that pea aphids alternatively splice 34% of their genes, a high percentage for invertebrates. We also find that there is extensive use of differential spliced events between genetically identical, polyphenic females. These differentially spliced events are enriched for exon skipping and mutually exclusive exon events that maintain the open reading frame, suggesting that polyphenic morphs use alternative splicing to produce phenotype-biased proteins. Many genes that are differentially spliced between polyphenic morphs have putative functions associated with their respective phenotypes. We find that the majority of differentially spliced genes is not differentially expressed genes. Our results provide a rich candidate gene list for future functional studies that would not have been previously considered based solely on gene expression studies, such as ensconsin in the reproductive polyphenism, and CAKI in the wing polyphenism. Overall, this study suggests an important role for alternative splicing in the expression of environmentally determined phenotypes.